Optimizing Customer Relationship Management Communication in Increasing Brand Awareness and Loyalty of Prestige Fixed and Mobile Customers at PT Telkomsel Medan - Al Azmi, Hana; Ginting, Rahmanita; Thariq, Muhammad (Persepsi: Communication Journal, 2025)
This study aims to analyze the optimization of Customer Relationship Management (CRM) communication in increasing brand awareness and customer loyalty at PT Telkomsel Medan and analyze its obstacles. The theory used in this study is the Human Relations Theory. The informants in this investigation are employees of PT Telkomsel Medan and prestige customers of PT Telkomsel Medan. The research method used is qualitative with data collection techniques through interviews and documentation. Data analysis is carried out through reduction, data presentation, conclusion drawing and to ensure the validity of the data using source triangulation. The results of the study show that PT Telkomsel Medan optimizes CRM communication, among others, taking advantage of every national and international momentum such as the Aquabike Event to introduce Telkomsel products, segment customers, provide rewards and loyalty to customers, provide MyTelkomsel applications that are useful to more easily reach customers, and collect customer data through the application Digital Smart Care (DSC) as well as employee performance evaluations every month. This approach not only increases brand awareness but also creates a harmonious and mutually beneficial relationship between the company and customers. PT Telkomsel Medan also experienced obstacles in the implementation of CRM activities, including in terms of technology, namely limited access  to the Digital Smart Care (DSC) application and human resources that arose due to miscommunication between PT Telkomsel Medan employees and customers.